Pungutan Pemerintah Desa Terhadap Masyarakat Sebagai Penyelenggaraan Pemerintahan Desa - Halsi, Klaudio; Nugroho, Rizal; Indrayati, Rosita (Lentera Hukum, 2015)
The original income of the village is income derived from the business of the village, the result of the village's assets, self-help and community participation, mutual assistance, and other village income. All revenues originating from original village revenues, regional revenue, and regional retribution, ADD, financial assistance from provincial and district / municipal governments, both general and specific, and non-binding third-party donations or contributions other legitimate village revenues must be recorded in an orderly manner. Other Original Revenues The villages are among others derived from village levies. The levies in the village are levies on the use of village halls, levies on prospective villagers, and so on. In Article 25 paragraph (1) of Regulation of the Minister of Home Affairs of the Republic of Indonesia Number 113 of 2014 concerning Village, Finance Management explains that the Village Government is prohibited from levies as acceptance of villages other than those stipulated in village regulations. KEYWORDS: Village levies, Authority of the village, Village government.